2014
DOI: 10.1002/2014gl059788
|View full text |Cite
|
Sign up to set email alerts
|

On vertical electric fields at lunar magnetic anomalies

Abstract: We study the interaction between a magnetic dipole mimicking the Gerasimovich magnetic anomaly on the lunar surface and the solar wind in a self-consistent 3-D quasi-neutral hybrid simulation where ions are modeled as particles and electrons as a charge-neutralizing fluid. Especially, we consider the origin of the recently observed electric potentials at lunar magnetic anomalies. An antimoonward Hall electric field forms in our simulation resulting in a potential difference of <300 V on the lunar surface, in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 14 publications
7
49
1
Order By: Relevance
“…Generally, these models, consistent with observations, have shown that strong magnetic anomalies may shield the lunar surface from solar wind and have a direct impact on surface weathering and swirl albedo markings [ Blewett et al , ; Poppe et al , ]. Recently, Jarvinen et al [] using a three‐dimensional hybrid model studied the interaction between a single magnetic dipole mimicking the Gerasimovich magnetic anomaly. Their studies, consistent with Chandrayaan‐1 ENA observations, estimated an electrostatic potential of <+300 V above the magnetic anomalies.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Generally, these models, consistent with observations, have shown that strong magnetic anomalies may shield the lunar surface from solar wind and have a direct impact on surface weathering and swirl albedo markings [ Blewett et al , ; Poppe et al , ]. Recently, Jarvinen et al [] using a three‐dimensional hybrid model studied the interaction between a single magnetic dipole mimicking the Gerasimovich magnetic anomaly. Their studies, consistent with Chandrayaan‐1 ENA observations, estimated an electrostatic potential of <+300 V above the magnetic anomalies.…”
Section: Introductionmentioning
confidence: 76%
“…Apart from observations, several attempts have been made to model the solar wind plasma interaction with lunar magnetic anomalies theoretically, numerically, and experimentally using single dipole [ Siscoe and Goldstein , ; Harnett and Winglee , , ; Poppe et al , ; Kallio et al , ; Wang et al , , ; Shaikhislamov et al , ; Jarvinen et al , ; Deca et al , ; Ashida et al , ] and multidipole [ Harnett and Winglee , ] approximations. Generally, these models, consistent with observations, have shown that strong magnetic anomalies may shield the lunar surface from solar wind and have a direct impact on surface weathering and swirl albedo markings [ Blewett et al , ; Poppe et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The computational investigation into mini-magnetospheres has become an area of considerable interest. A number of papers on hybrid (Bamford et al 2008;Gargaté et al 2008;Kallio et al 2012;Poppe et al 2012) and particle-in-cell (PIC) (Kallio et al 2012;Bamford et al 2013aBamford et al , 2013bBamford et al , 2015Deca et al 2014Deca et al , 2015Jarvinen et al 2014;Cruz et al 2015Cruz et al , 2016Dyadechkin et al 2015;Fatemi et al 2015) simulations have been authored, following from previous magnetohydrodynamic (MHD) simulations (Harnett & Winglee 2002Kurata et al 2005). Here we perform fully self-consistent PIC simulations in 2D and 3D, with a realistic proton-to-electron mass ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Some numerical simulations using a particle model have focused on this phenomenon. [8][9][10] We have another interesting example, this one from space engineering, of the interaction of plasma flow with a smallscale magnetic dipole. The magnetic sail 11 and the magnetoplasma sail (MPS) 12 have been proposed as possible systems for interplanetary flight.…”
Section: Introductionmentioning
confidence: 99%